El Niño in World History - Grove, Richard (Palgrave Studies in World Environmental History, 2018)
This book examines the role of the El Niño Southern Oscillation (ENSO) in society. Throughout human history, large or recurrent El Niños could cause significant disruption to societies and in some cases even contribute to political change. Yet it is only now that we are coming to appreciate the significance of the phenomenon. In this volume, Richard Grove and George Adamson chart the dual history of El Niño: as a global phenomenon capable of devastating weather extremes and, since the 18th century, as a developing idea in science and society. The chapters trace El Niño's position in world history from its role in the revolution in Australian Aboriginal Culture at 5,000 BP to the 2015-16 'Godzilla' event. It ends with a discussion of El Niño in the current media, which is as much a product of the public imagination as it is a natural process.